A 1.8‐kb insertion in the 3′‐UTR of RXFP2 is associated with polledness in sheep. (23rd June 2015) - Wiedemar, Natalie; Drögemüller, Cord
Summary Sheep breeds show a broad spectrum of different horn phenotypes. In most modern production breeds, sheep are polled (absence of horns), whereas horns occur mainly in indigenous breeds. Previous studies mapped the responsible locus to the region of the RXFP2 gene on ovine chromosome 10. A 4‐kb region of the 3′‐end of RXFP2 was amplified in horned and polled animals from seven Swiss sheep breeds. Sequence analysis identified a 1833‐bp genomic insertion located in the 3′‐UTR region of RXFP2 present in polled animals only. An efficient PCR‐based genotyping method to determine the polled genotype of individual sheep is presented. Comparative sequence analyses revealed evidence that the polled‐associated insertion adds a potential antisense RNA sequence of EEF1A1 to the 3′‐end of RXFP2 transcripts.